Improved vehicle-to-home (iV2H) operation mode: experimental analysis of the electric vehicle as off-line UPS - Monteiro, Vítor Duarte Fernandes (2017)
This paper presents experimental results of electric vehicle (EV) operation as an off-line uninterruptible power supply (UPS). Besides the traditional grid-to-vehicle and vehicle-to-grid modes, this paper presents an improved vehicle-to-home operation mode. This new operation mode consists of the detection of a power outage in the power grid and the change of the EV battery charger control to operate as an off-line UPS. When the power grid voltage is restored, the voltage produced by the on-board EV battery charger is slowly synchronized with the power grid voltage before a complete transition to the normal mode. This paper presents results of two algorithms to detect a power outage: the root mean square (rms) calculation method based on half-cycle of the power grid voltage, and the rms estimation based on a Kalman filter. The experimental results were obtained in steady and transient state considering two cases with the EV plugged in at home:when charging the batteries and without charging the batteries. This paper describes the EV battery charger, the power outage detection methods, and the voltage and current control strategies.